(untitled) (Journal of educational development exploration, 2026)
Against the macro background of deep integration between higher education and vocational education, the rapid development of artificial intelligence (AI) technology offers new theoretical perspectives and practical pathways for transforming and restructuring the training model of vocational faculty in university mechanical programs. Based on constructivist learning theory, teacher professional development theory, and the intrinsic logic of technology-enabled education, this paper systematically analyzes the core issues in the current training of vocational faculty in mechanical programs, including outdated knowledge structures, disconnection from practical abilities, and insufficient teaching adaptability. By introducing AI technologies with core capabilities such as context awareness, adaptive learning, intelligent assessment, and virtual simulation, it is possible to construct a multidimensional empowerment pathway, which runs from data-driven diagnosis of teacher competencies to intelligent personalized training programs, then to integrated practical training environments, and finally to continuous and dynamic professional development support. This pathway aims to transition faculty training from experience-oriented to data-intelligence-oriented, significantly enhancing teachers’ abilities in instructional design, technology application, and professional reflexivity in complex engineering contexts. The study further points out that AI empowerment is not merely a technological addition, but involves a systematic reshaping of educational philosophy, curriculum systems, evaluation mechanisms, and organizational culture. Future exploration is needed in ethical standards, human-computer collaboration mechanisms, and interdisciplinary faculty development to advance the training system for mechanical program vocational faculty toward greater intelligence, personalization, and ecological integration.